2016
DOI: 10.1002/ijc.30234
|View full text |Cite
|
Sign up to set email alerts
|

Targeting atypical protein kinase C iota reduces viability in glioblastoma stem‐like cells via a notch signaling mechanism

Abstract: In a previous study, Protein Kinase C iota (PRKCI) emerged as an important candidate gene for glioblastoma (GBM) stem-like cell (GSC) survival. Here, we show that PKCι is overexpressed and activated in patient derived GSCs compared with normal neural stem cells and normal brain lysate, and that silencing of PRKCI in GSCs causes apoptosis, along with loss of clonogenicity and reduced proliferation. Notably, PRKCI silencing reduces tumor growth in vivo in a xenograft mouse model. PKCι has been intensively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…These results suggest that PKCλ, but not PKCζ, is involved in c-Met-dependent cell proliferation and tumor formation, as well as other actions of ALDH1-positive breast CSCs. Remarkably, PKCλ controls the Notch signal pathway, a key driver of stemness in KRAS-mediated lung adenocarcinoma (LADC) (43) and in glioblastoma (44). In addition, PKCλ controls signaling by SOX2-hedgehog acyl transferase (HHAT), a master transcriptional regulator of stemness, in lung squamous cell carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PKCλ, but not PKCζ, is involved in c-Met-dependent cell proliferation and tumor formation, as well as other actions of ALDH1-positive breast CSCs. Remarkably, PKCλ controls the Notch signal pathway, a key driver of stemness in KRAS-mediated lung adenocarcinoma (LADC) (43) and in glioblastoma (44). In addition, PKCλ controls signaling by SOX2-hedgehog acyl transferase (HHAT), a master transcriptional regulator of stemness, in lung squamous cell carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Notch signaling dysregulation has also been recognized in glioblastoma CSCs [82]. It was found that Protein Kinase C Iota (PKCi) was highly expressed in glioblastoma patient-derived CSCs, and silencing PKCi resulted in apoptosis and reduction of proliferation of the glioblastoma CSCs in vitro and tumor growth in vivo in a xenograft mouse model [83]. Gene expression profiling of PKCi-silenced glioblastoma CSCs revealed a novel role of the Notch signaling pathway in PKCi mediated glioblastoma CSC's survival [83].…”
Section: Signaling Pathways In Cscsmentioning
confidence: 99%
“…It was found that Protein Kinase C Iota (PKCi) was highly expressed in glioblastoma patient-derived CSCs, and silencing PKCi resulted in apoptosis and reduction of proliferation of the glioblastoma CSCs in vitro and tumor growth in vivo in a xenograft mouse model [83]. Gene expression profiling of PKCi-silenced glioblastoma CSCs revealed a novel role of the Notch signaling pathway in PKCi mediated glioblastoma CSC's survival [83]. In addition to its important roles in CSCs, Notch signaling is also involved in EMT to promote cancer cell acquisition of a stem-like phenotype and drug resistance.…”
Section: Signaling Pathways In Cscsmentioning
confidence: 99%
“…Following genes were targeted: TP53 (gRNA: GT GAG GCT CCC CTT TCT TG), LIG4 (gRNA: GAC GGA AAA GAT ACC TCG G). Virus production and transduction as described previously 27 ; in brief, pLentiV2, pDMDG.2, and pSPAX were co-transfected in HEK293T cells, and viruscontaining supernatant was concentrated by ultra-centrifugation. Transduction was done by adding concentrated virus particles to both NSC cell lines for 24hours, after which cells were maintained under selection either with puromycin or blasticidin at 2ug/mL for at least 2 weeks.…”
Section: Crispr-cas Targeted Gene Disruptionmentioning
confidence: 99%